(untitled) (Fiep Bulletin - online, 2015)
Different local characteristics and realities are found even in regions located in the same place or city. This issue can be strongly confirmed by the fact that different habits, lifestyles and work are found in these same regions. Nowadays, the space between rural and urban areas environmental conditions is becoming bigger and bigger due to the improvement of technology and increasing of violence and people’s needs. This situation also occurs inside the schools, where there are many problems of structure, teachers and illiteracy percentage (worse in rural schools). The aim of this study is to quantify the results found in both places by showing data about body composition, motor skills and physical fitness of school children from middle school (5th to 8th grade) from urban and rural areas, finding explanations for this diversity and so provide means to improve the physical fitness and life quality of the children in and out of the school environment.